The socialism as a hypertrophy of the individualism. Lev Karsavin's reception of Karl Marx's ideas on the example of the considerations about the progress - Ostrowski, Andrzej (Hybris, 2018)
Lev Karsavin (1882-1952) on the views of Karl Marx (1818-1882) spoke indirectly, through analysis of socialism as a scientific theory, and then as the ideological doctrine, which determines, inter alia, the form of the State and the life of the individual human being. Special attention deserves both the form of expression on the theme of socialism and the way of its understanding. The goal of the article is to discuss Karsavin's reception of Marx's ideas and also to draw attention to theoretical consequences of this reception.